ANALISIS KOMPARATIF METODE FATWA MUI DAN DÂR AL-IFTÂ MESIR - Muhammad Amrul Irsyadi; Asmuni, Asmuni (Muẚṣarah: Jurnal Kajian Islam Kontemporer, 2023)
This article discusses the comparison of the fatwas Indonesian Ulema Council method and the Egyptian dar ifta method for generating arguments to produce laws. The legal conclusion (istinbâth) methodology was then tested on contemporary fatwas. The research method used in this study is library research, which examines the comparative method of the fatwa method between the Indonesian Ulema Council and the Dar Ifta of Egypt. The sources for this study are the Egyptian Dar Ifta website, the official Indonesial Ulema website, and books related to fatwa wording. The reference source for the fatwa methodology in this study is the topical issue regarding the speeding up of zakat (obligatory charity) time and the distribution of zakat to non-Muslims in Indonesian Ulema Council Fatwa Circular No. 23 of 2020 and Fatwa Dar Ifta Number 1649. The results of this study show that there are similarities in the methodological steps involved in issuing fatwas between the two institutions, such as conducting a search for the opinions of classical Muslim scholars contained in the heritage book (turâts). However, methodological differences can be seen in the phases that have been completed. The Dar Ifta of Egypt has four stages for judging contemporary fatwas: Tashwîr (conception), Takyîf (Adaptation), Hukm (Law), and Ifta. Meanwhile, Indonesian Ulema Council performs collective ijtihad with the ijtihad rule using Bayâni, the Ta'lîli method (Qiyâsi, Istihsâni, Ilhâqi), Istiṣlâhi, and Sad Al-Dzarî'ah Keywords: Fatwa; MUI; dar Ifta   Abstrak: Artikel ini menganalisis perbandingan metode fatwa MUI dan dâr Ifta Mesir tentang cara penggalian dalil hingga melahirkan hukum. Metodologi istinbâth hukum tersebut kemudian diuji coba pada fatwa kontemporer. Kajian ini menggunakan metode penelitian pustaka (library research) yang mengkaji perbandingan (comparative method) metode fatwa antara lembaga MUI dan dâr Ifta Mesir. Sumber kajian ini adalah website dâr Ifta Mesir, website resmi MUI dan buku-buku yang berkaitan dengan formulasi fatwa. Sumber referensi untuk metodologi fatwa dalam penelitian ini adalah isu kontemporer mengenai penyegeraan waktu zakat dan distribusi zakat kepada non muslim dalam edaran fatwa MUI No. 23 tahun 2020 dan fatwa dâr Ifta nomor 1649. Hasil dari penelitian ini mengungkap bahwa terdapat kesamaan langkah metodologi dalam memberikan fatwa diantara kedua lembaga seperti melakukan penelusuran pendapat ulama muslim klasik yang termuat dalam kitab turats. Perbedaan metodologi terlihat pada langkah fase-fase yang ditempuh. Dâr Ifta Mesir memiliki empat langkah dalam menghukumi fatwa kontemporer yaitu fase tashwîr, takyîf, hukm, dan ifta. Sedangkan MUI melakukan ijtihad kolektif dengan rule ijtihad dengan metode bayâni, ta’lîli (qiyâsi, istihsâni, ilhâqi), istishlâhi, dan sad al-Dzarî’ah. Kata Kunci: Fatwa; MUI; dar Ifta